2014
DOI: 10.3109/14397595.2014.990409
|View full text |Cite
|
Sign up to set email alerts
|

Short-term add-on tocilizumab and intravenous cyclophosphamide exhibited a remission-inducing effect in a patient with systemic lupus erythematosus with refractory multiorgan involvements including massive pericarditis and glomerulonephritis

Abstract: We report on a 41-year-old woman with refractory systemic lupus erythematosus with massive pericarditis, macrophage activation syndrome, and glomerulonephritis despite high-dose glucocorticoids and tacrolimus. Tocilizumab dramatically improved pericarditis, and glomerulonephritis was controlled after adding cyclophosphamide. We had to halt tocilizumab and cyclophosphamide due to possible pneumocystis infection after five and three infusions of tocilizumab and intravenous cyclophosphamide, respectively. Neverth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…This raises the possibility that cytokine‐directed treatment with biologic agents could serve as an effective treatment for MAS. Indeed, there are several reports of MAS treated with high doses of anakinra , and scattered reports of treatment with tocilizumab . However, this systematic review demonstrates that MAS also occurs with regularity on these biologic agent treatments and therefore suggests that other pathways may be more central to MAS pathogenesis in various patient populations.…”
Section: Discussionmentioning
confidence: 82%
“…This raises the possibility that cytokine‐directed treatment with biologic agents could serve as an effective treatment for MAS. Indeed, there are several reports of MAS treated with high doses of anakinra , and scattered reports of treatment with tocilizumab . However, this systematic review demonstrates that MAS also occurs with regularity on these biologic agent treatments and therefore suggests that other pathways may be more central to MAS pathogenesis in various patient populations.…”
Section: Discussionmentioning
confidence: 82%
“…14 However, an IL-17 inhibitor has not been considered for the clinical treatment of lupus patients. 15 An IL-6 receptor antagonist, tocilizumab, induced short-term disease remission in some cases of lupus nephritis 16,17 but with high rate of relapse after long-term follow-up, 18 suggesting that directly inhibiting Th17 cells and its related cytokines was not appropriate for lupus treatment. A recent study by Schmidt et al showed that IL-17A deficiency did not affect the morphological or functional parameters in MRL/lpr mice with lupus nephritis, nor did IL-17A neutralization affect the clinical course of nephritis in NZB/NZW mice, suggesting that the Th17/IL-17A immune response plays no major role in the immunopathogenesis of lupus nephritis in MRL/lpr and NZB/NZW mice.…”
Section: Discussionmentioning
confidence: 98%
“…IL-6 induces the expression of IL-23R and RORγt, thus promoting the generation of Th17 cells from naïve T cells together with TGF-β while inhibits TGF-β induced Treg (iTreg) differentiation (33). It has been reported that IL-6 levels are increased in various autoimmune diseases including rheumatoid arthritis (RA), multiple sclerosis (MS) and lupus (34), and targeting IL-6 can be an effective approach in the treatment of several autoimmune diseases (35,36). Here we demonstrated for the first time that increased IL-6 might be induced by impaired let-7f in SLE BM-MSCs, which might led to IL-6-STAT3-NF-κB pro-inflammatory circuit, and thus contribute to lupus development.…”
Section: Discussionmentioning
confidence: 99%